Multi-trajectories of systolic and diastolic hypertension and coronary heart disease in middle-aged and older adults - Li, Mingzhuo; Zhou, Miao; Yang, Yang; Liu, Yafei; Yin, Chaonan; Geng, Wenting; Wang, Chunxia; Tang, Fang; Zhao, Yang; Xue, Fuzhong; Sun, Xiubin; Yuan, Zhongshang (Frontiers in Public Health, 2022)
Objective: To investigate multi-trajectories of systolic and diastolic hypertension and assess their association with risk of coronary heart disease (CHD) in middle-aged and older Chinese adults. Methods: The study cohort comprised 4102 individuals aged 40 to 75 years with records of at least 4 systolic blood pressure (SBP) and diastolic blood pressure (DBP) records. A group-based multi-trajectory model was adopted to identify multi-trajectories of systolic and diastolic hypertension, followed by a logistic model to assess the independent associations between these trajectories and CHD risk. Multinomial logistic model was used to evaluate the impact of baseline covariates on trajectory groups. Results: 6 distinct trajectories for systolic and diastolic hypertension were identified which represent distinct stages of hypertension and were characterized as low-stable, low-increasing, medium-decreasing, medium-increasing-decreasing, isolated systolic hypertension phase and high-decreasing. Compared with the low-stable group, the adjusted odds ratios (ORs) and 95% confidence intervals (CIs) were 2.23 (1.34-3.70) for the medium-increasing-decreasing group, 1.87 (1.12-3.11) for the high-decreasing group after adjustment for baseline covariates. Compared with the low-increasing group, the ORs and 95% CIs were 1.88 (1.06-3.31) for the medium-increasing-decreasing group. Age, gender, drinking, body mass index (BMI), triglyceride (TG), fasting plasma glucose (FPG) were independent predictors for trajectory group 4 and group 6. Conclusions: Novel, clinically defined multi-trajectories of systolic and diastolic hypertension were identified. Middle-aged and older adults with medium-increasing-decreasing or high-decreasing blood pressure trajectories are potentially critical periods for the development of CHD, preventing adverse changes in hypertension status and reducing high risk of CHD is necessary for people in distinct trajectory groups.